2010
DOI: 10.1088/0022-3727/43/35/354003
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural origins of localization in InGaN quantum wells

Abstract: The startling success of GaN-based light emitting diodes despite the high density of dislocations found in typical heteroepitaxial material has been attributed to localisation of carriers at non-uniformities in the quantum wells which form the active region of such devices. Here, we review the different possible structures within the quantum wells which could act as localisation sites, at length scales ranging from the atomic to the tens of nanometre range. In some quantum wells several localisation mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 47 publications
0
65
2
Order By: Relevance
“…Along this line, Kehagias et al [11] have shown that for lower growth temperatures of the (In,Ga)N insertions, the inhomogeneity of the alloy is further increased and the width of the (In,Ga)N band for the NW ensemble can amount to 800 meV. A certain degree of localization might well be necessary to avoid the possibility of detrimental carrier recombination at the NW surface in line with what is discussed for dislocations in planar layers [48]. However, strong inhomogeneities impede the desired tunability of emission properties [9].…”
Section: Single Nw Photoluminescencementioning
confidence: 75%
“…Along this line, Kehagias et al [11] have shown that for lower growth temperatures of the (In,Ga)N insertions, the inhomogeneity of the alloy is further increased and the width of the (In,Ga)N band for the NW ensemble can amount to 800 meV. A certain degree of localization might well be necessary to avoid the possibility of detrimental carrier recombination at the NW surface in line with what is discussed for dislocations in planar layers [48]. However, strong inhomogeneities impede the desired tunability of emission properties [9].…”
Section: Single Nw Photoluminescencementioning
confidence: 75%
“…The reason that InGaN LEDs are much more tolerant of TDs than other conventional III-V materials is probably due to carrier localisation effects [20][21][22][23][24][25][26]. The first contributing factor is the monolayer height interface steps on the InGaN quantum wells.…”
Section: à2mentioning
confidence: 99%
“…The (a+c)-type cores were studied because they are (a) easier to locate than a-type cores, (b) present in our samples in proportions (in contrast to the pure ctype cores which comprise only ~1% of all dislocations in our samples), (c) they reveal the effects of both a-type and c-type Burgers vectors components and (d) the highest energetic stabilization of In segregation is predicted for this core type and therefore it is most likely to be observed experimentally. for In x Ga 1-x N epilayers 57 , with a side length of approximately 40 nm. Precise identification of the core configuration is not possible due to ambiguous contrast at the core, which could be consistent with a disrupted, rather than highly symmetrical, core configuration consistent with the highly segregated In-rich cores predicted as seen in Figure 3(c).…”
mentioning
confidence: 99%